Pollution sources and metallic elements mobility recorded by heavy minerals in soils affected by Cu-smelting (Legnica, SW Poland) - Tyszka Rafał; Pietranik Anna; Marciniak-Maliszewska Beata; Kierczak Jakub (Mineralogia)
Heavy mineral particles are widely used in Earth science studies to show sediment provenance and weathering conditions. Such particles are particularly useful in polluted soils surrounding mining and smelting facilities because heavy minerals are common by-products of these activities and may accumulate in the soils. As such, the particles are suitable indicators of metallic element carriers and their stability in the soil environment. In this study, we analyze heavy mineral particles in two soils surrounding the active copper smelter (Legnica, SW, Poland). We show that particles associated with different smelting activities dominate the heavy mineral fraction. We note the general absence of sulfides in the fraction indicating that these minerals might have been entirely dissolved, but timing of this dissolution is uncertain (before or after deposition within soils). Currently, the carriers of potentially toxic elements are mainly secondary Fe oxides. Studies aiming at better estimation of the proportion of metallic elements contained in heavy mineral particles are needed to fully use the potential of these phases in polluted soil studies. We estimate that Pb contained in Pb-rich silicate glass constitutes <0.5% of the total Pb budget and Pb contained in secondary Fe oxides is over 1% of the total budget, but these are minimal estimates.